Credit Rating Agencies in the Face of the War in Ukraine - Wołoszczenko-Hołda, Łada; Niedziółka, Paweł (Agencje ratingowe wobec wojny w Ukrainie, 2023)
The aim of this study was to find evidence of whether the ratings prior to Russia’s reinvasion of Ukraine in 2022 reflected the geopolitical risks, and if the rating actions taken in response to the aggression accurately informed the financial market participants of the conflict’s spillover impacts, transmitting them to the credit risk assessment. The rating actions in response to the Russia’s reinvasion in 2022 indicate a considerable shock from the underestimation of geopolitical and political risks in Russia, including autocracy risks. The pattern of the rating actions differed from those in response to the invasion in 2014, and also varied from those used over the past two decades during the outbreak of crises with underlying economic drivers. The CRAs signalled a high level of geopolitical uncertainty which may involve a necessary shift to ‘point-in-time’ ratings, as ‘through-the-cycle’ ratings could have little relevance due to the lasting geopolitical risk.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 2, s. 145-160
Keywords: credit rating agency; rating; war in Ukraine; Big Three; agencja ratingowa; wojna w Ukrainie; Wielka Trójka